Oxidative stress and use of antioxidants in fish semen cryopreservation - Leydy Sandoval‐Vargas; Mauricio Silva Jiménez; Jennie Risopatrón González; Elías Figueroa Villalobos; Elsa Cabrita; Iván Valdebenito Isler (Reviews in Aquaculture, 2021)
Reactive oxygen species (ROS) have been proposed as one of the main causes of the impairment of fish spermatozoa integrity and functionality during cryopreservation. The high content of unsaturated fatty acids in sperm cells and the low antioxidant capacity of diluted semen are key factors in making sperm cells susceptible to ROS attacks. For this reason, some recent studies have determined the antioxidant status of the seminal plasma and spermatozoa of fish species. Additionally, some studies have evaluated the effects of antioxidants on post‐thaw sperm quality. Although ROS are certainly involved in sperm damage, other factors, such as ice crystal formation, seem to play a crucial role in cryodamage. This challenge has not yet been resolved because both the endogenous antioxidant capacity of the semen and its response to different supplementation practices seem to present specific inter‐ and intraspecies characteristics and effects. This review summarises knowledge on antioxidant defence and oxidative stress in fish semen, as well as antioxidant supplementation in cryopreservation media, in order to establish perspectives for future studies.